2004
DOI: 10.1111/j.0269-8463.2004.00924.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing foraging behaviour of small and large honey‐bee colonies by decoding waggle dances made by foragers

Abstract: Summary 1.We compared the foraging behaviour of two small (approximately 6000 bees) and two large (approximately 20 000 bees) honey-bee colonies over 6 days. We determined where the bees of each colony foraged, whether they collected nectar or pollen, the number of patches foraged at, the number of bees engaged in foraging, and the concentration of the nectar collected. 2. Even though the colonies were located in the same environment and had the same genetic background, foragers from different colonies used di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(73 citation statements)
references
References 17 publications
3
69
0
1
Order By: Relevance
“…A positive correlation was found between the foraging activity and the brood area, and between the foraging activity and the bee numbers. This evidence also supported that of Beekman et al (2004), who found that small colonies had lower numbers of foragers returning per minute than large colonies. A moderate positive correlation was found between the foraging activity and the stored pollen area.…”
Section: Foraging Activitysupporting
confidence: 87%
“…A positive correlation was found between the foraging activity and the brood area, and between the foraging activity and the bee numbers. This evidence also supported that of Beekman et al (2004), who found that small colonies had lower numbers of foragers returning per minute than large colonies. A moderate positive correlation was found between the foraging activity and the stored pollen area.…”
Section: Foraging Activitysupporting
confidence: 87%
“…At the start of a simulation, the hive (containing all bees) is placed in the centre of an 8 3 8 km map (64 km 2 ). This area was chosen because more than 90% of foraging trips typically occur within 4 km of a hive (Beekman et al, 2004;Seeley, 1995;Visscher and Seeley, 1982). During the simulation, the behavioral state and variables are updated for each bee in turn (in a randomized order) at every time step.…”
Section: Methodsmentioning
confidence: 99%
“…This was varied from 2.5 to 80 ll (the maximum capacity of the honey bee crop, Frisch, 1967), and the energy content of nectar was assumed to be 5.819 J/ll (about 30% sugar per weight, which is a typical value, Seeley, 1985). Empirical studies show that the typical amount collected by bees from natural food sources varies mostly from 10 to 30 ll per trip (and thus per patch; Beekman et al, 2004;Roubik et al, 1986;Seeley 1985Seeley , 1995Thom et al, 2000, Dornhaus A and Chittka L, unpublished data). Although the definition of ''quality'' just given thus relates to nectar volume, it can equally be thought of as representing sugar concentration or total sugar mass (incorporating concentration and volume).…”
Section: Resource Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Workers in smaller colonies have sometimes been predicted to work harder (Houston et al 1988;Franks and Partridge 1993), whereas another study predicts higher workload in larger colonies (Schmid-Hempel 1990). Empirical support seems equivocal, with some support for higher individual effort in smaller (Fewell et al 1991;London and Jeanne 2003) or larger colonies (Schmid-Hempel 1990;Herbers and Choiniere 1996;Plowes and Adams 2005), and some studies finding no clear effect (Wolf and Schmid-Hempel 1990;Beekman 2004). What is the effect of colony size on individual workload, and are larger colonies likely to have a more skewed workload distribution, creating some highly active and many inactive workers?…”
Section: Introductionmentioning
confidence: 99%